AAV-BDNF gene therapy ameliorates a hypothalamic neuroinflammatory signature in the Magel2-null model of Prader-Willi syndrome - Nicholas J. Queen; Wei Huang; Xunchang Zou; Xiaokui Mo; Lei Cao (Molecular Therapy: Methods & Clinical Development, 2023)
Individuals with Prader-Willi syndrome (PWS) exhibit several metabolic and behavioral abnormalities associated with excessive food-seeking activity. PWS is thought to be driven in part by dysfunctional hypothalamic circuitry and blunted responses to peripheral signals of satiety. Previous work described a hypothalamic transcriptomic signature of individuals with PWS. Notably, PWS patients exhibited downregulation of genes involved in neuronal development and an upregulation of neuroinflammatory genes. Deficiencies of brain-derived neurotrophic factor (BDNF) and its receptor were identified as potential drivers of PWS phenotypes. Our group recently applied an adeno-associated viral (AAV)-BDNF gene therapy within a preclinical PWS model, Magel2-null mice, to improve metabolic and behavioral function. While this proof-of-concept project was promising, it remained unclear how AAV-BDNF was influencing the hypothalamic microenvironment and how its therapeutic effect was mediated. To investigate, we hypothalamically injected AAV-BDNF to wild type and Magel2-null mice and performed mRNA sequencing on hypothalamic tissue. Here, we report that (1) Magel2 deficiency is associated with neuroinflammation in the hypothalamus and (2) AAV-BDNF gene therapy reverses this neuroinflammation. These data newly reveal Magel2-null mice as a valid model of PWS-related neuroinflammation and furthermore suggest that AAV-BDNF may modulate obesity-related neuroinflammatory phenotypes through direct or indirect means.